Retrospective analysis of complications in 3600 patients of laparoscopic cholecystectomy - Resutra, Ritvik; Gupta, Rajive; Gupta, Madhu (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy results in specific complications which occur frequently as compared to open cholecystectomy. Several aspects of these complications and their treatment modalities were analyzed. Methods: 3600 cases of laparoscopic cholecystectomy performed by a single surgeon at various private hospitals in Jammu (Jammu and Kashmir), India during the period of 18 years from March 2002 to March 2020 were analyzed for the complications and their management. Results: Complications of laparoscopic cholecystectomy occurred in 14.5% of the patients. The most common complication was haemorrhage. Conversion to open cholecystectomy was necessary in 41 (1.13%) patients due to obscure anatomy as a result of adhesions and acute inflammation. In the study, 6 deaths (0.16%) were recorded. Conclusions: Laparoscopic surgeon should remain highly vigilant to detect major complications like injury to small gut at the time of entry into the peritoneal cavity or bile duct injury during laparoscopic cholecystectomy at an earliest and should timely manage such cases to save the life of the patient.